Combination of immune checkpoint blockade with DNA cancer vaccine induces potent antitumor immunity against P815 mastocytoma - Lopes, A; Vanvarenberg, K; Kos, S; Lucas, S; Colau, D; Van Den Eynde, BJ; Préat, V; Vandermeulen, G (Nature Publishing Group, 2018)
DNA vaccination against cancer has become a promising strategy for inducing a specific and longlasting antitumor immunity. However, DNA vaccines fail to generate potent immune responses when used as a single therapy. To enhance their activity into the tumor, a DNA vaccine against murine P815 mastocytoma was combined with antibodies directed against the immune checkpoints CTLA4 and PD1. The combination of these two strategies delayed tumor growth and enhanced specific antitumor immune cell infiltration in comparison to the corresponding single therapies. The combination also promoted IFNg, IL12 and granzyme B production in the tumor microenvironment and decreased the formation of liver metastasis in a very early phase of tumor development, enabling 90% survival. These results underline the complementarity of DNA vaccination and immune checkpoint blockers in inducing a potent immune response, by exploiting the generation of antigen-specific T cells by the vaccine and the ability of immune checkpoint blockers to enhance T cell activity and infiltration in the tumor. These findings suggest how and why a rational combination therapy can overcome the limits of DNA vaccination but could also allow responses to immune checkpoint blockers in a larger proportion of subjects.